2020
DOI: 10.9734/jpri/2020/v32i2130749
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Screening to Identify the Protein Targets in Common Dental Pathogens Interacting with Menthol

Abstract: Deducing the molecular pathway underlying the antimicrobial effect of phytocompounds is an inevitable part of drug discovery. Selection of potential targets on the microbial pathogens will eventually lead to eradication of microbes and effective treatment. In this context, the present insilico study identifies vital targets in the dental pathogens interacting with menthol. The STITCHtool was used for identifying the protein drug interaction, VICMPred and VirulentPred tools were used for identifying the functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…Another study performed by Balamithra, et al in the year 2020, targeted proteins on the dental pathogens which were shown to interact with glycyrrhizin which was similar to our study [38]. Other research was done to see the protein interaction of red complex pathogens with Catechin, menthol and genistein [39][40][41].…”
Section: Discussionsupporting
confidence: 80%
“…Another study performed by Balamithra, et al in the year 2020, targeted proteins on the dental pathogens which were shown to interact with glycyrrhizin which was similar to our study [38]. Other research was done to see the protein interaction of red complex pathogens with Catechin, menthol and genistein [39][40][41].…”
Section: Discussionsupporting
confidence: 80%
“…The removal of these pathogens from the infection site is still a challenge. In silico tools have been largely used to cut down the primary cost of screening active molecules for their antimicrobial effect [22]. Gomez, et al investigated the inhibitory and lethal effect of triclosan against several microorganisms at different stages of their phase of population growth.…”
Section: Resultsmentioning
confidence: 99%
“…Several in silico studies have been performed to predict the potential targets of microbial pathogens against the drug selected [21][22][23]…”
Section: Resultsmentioning
confidence: 99%
“…Numerous reports have suggested the emergence of novel drug resistant pathogens in dental settings [1,2]. Phytocompounds, compounds from marine and animal sources and non-antibiotic drugs were repurposed for use as antimicrobial agents [3,4,5,6]. Antimicrobial peptides are small molecules which have opened a new era of peptide therapeutics.…”
Section: Introductionmentioning
confidence: 99%